2020
DOI: 10.30994/jqph.v4i1.140
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Social Cognitive Theory-Based Psychoeducation Towards Depression and Blood Pressure of Ischemic Stroke Patients

Abstract: Introduction. Stroke places on the third rank in the world as the cause of death. Depression is a common psychology condition found in ischemic stroke patient and generally experienced hypertension. The aim of this research is to analyze the effect of social cognitive theory-based psychoeducation towards depression and blood pressure of ischemic stroke patient. Design. The design of this research is quasi-experiment by pre and post control group within. The population is 100 ischemic stroke patients in mental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…This study found that the satisfaction scores [23] have conducted comprehensive nursing intervention on patients with ischemic stroke and found that the comprehensive nursing intervention group is significantly higher than the control group, and the cognition of the disease is relatively high. This is mainly because patients are optimistic after treatment with standardized education, and actively cooperate with doctors to significantly improve the curative effect and effectively improve the treatment effect of patients [24][25][26]. Therefore, health standardized education should be carried out in the treatment of patients with ischemic stroke, and psychological counseling and rehabilitation training should be included in the treatment of patients with ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that the satisfaction scores [23] have conducted comprehensive nursing intervention on patients with ischemic stroke and found that the comprehensive nursing intervention group is significantly higher than the control group, and the cognition of the disease is relatively high. This is mainly because patients are optimistic after treatment with standardized education, and actively cooperate with doctors to significantly improve the curative effect and effectively improve the treatment effect of patients [24][25][26]. Therefore, health standardized education should be carried out in the treatment of patients with ischemic stroke, and psychological counseling and rehabilitation training should be included in the treatment of patients with ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…The physiology of blood pressure starts with the heart pushing blood through the arteries. The blood exerts pressure on the artery walls (Mahyuvi & Nursalam, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Based on WHO (Word Health Organization) data, stroke is the 5th cause of death in America, reaching 129 thousand people per year. Stroke patients in the United States aged between 55-64 years as much as 11% have silent cerebral infarction, the prevalence increases to 40% at the age of 80 years and 43% at the age of 85 years (Mahyuvi & Nursalam, 2020). The prevalence of stroke in Indonesia has increased from 7% in the 2018 Riskesdas to 10.9% in 2020.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of stroke in Indonesia has increased from 7% in the 2018 Riskesdas to 10.9% in 2020. The prevalence of stroke in East Java Province is ranked 3rd in Indonesia, reaching 302,987 sufferers (Mahyuvi & Nursalam, 2020).…”
Section: Introductionmentioning
confidence: 99%